Chelating agents action on rat prostate - Yu. V. Yeschenko; V. V. Novitsky; V. D. Bovt; V. A. Yeschenko; O. I. Urazova (Бюллетень сибирской медицины)
It was shown in experiments on rats, that dithizone induced zinc deficiency in prostate cells. Three phase type of fluctuations of cytochemically detected zinc concentration was observed in the cells: phase of primary decrease, phase of temporary partial restoration and the phase of secondary decrease. Sodium diethyldithiocarbamate unlike to dithizone didn’t induce damage of cells and secondary decrease zinc content in its.